1982
DOI: 10.1007/bf00989105
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic research of subtropical vegetation in Taiwan II. Comparative exclusion of understory byPhyllostachys edulis andCryptomeria japonica

Abstract: On many hillsides of Taiwan there is a unique pattern of weed exclusion byPhyllostachys edulis (bamboo) andCryptomeria japonica (conifer) in which the density, diversity, and dominance of understory species are very different. Although the physical conditions of light, soil moisture, and soil nutrients strongly favor the growth of understory in a bamboo community, the biomass of its undergrowth is significantly low, indicating that physical competition among the understory species in the bamboo and conifer com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Chou and Yang (1982) suggested that bamboos interfere with the regeneration of herb species in Taiwan through production of allelopathic substances from their leaves. It is possible that this may also have reduced tree seed germination and seedling establishment in our study area.…”
Section: Discussionmentioning
confidence: 99%
“…Chou and Yang (1982) suggested that bamboos interfere with the regeneration of herb species in Taiwan through production of allelopathic substances from their leaves. It is possible that this may also have reduced tree seed germination and seedling establishment in our study area.…”
Section: Discussionmentioning
confidence: 99%
“…Allelopathic compounds released from bamboo ( Phyllostachys edulis (Carr.)) leaves can reduce the seedling abundance and species richness and then to prevent the growth of understory plants, thus reducing litter; this would also reduce the input of SOC in the bamboo forest (Chou and Yang 1982; Chang and Chiu 2015). Meanwhile, the diversity and composition of soil bacterial communities could be different in coniferous plantations and croplands, which could affect the SOC decomposition rate and then the SOC stocks.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al (1997) highlighted that each canopy tree species is a physical ecosystem engineer that creates many specific abiotic conditions beneath its crown, like specific litter accumulation, soil composition, allelochemical compounds composition, among others (for details see Zinke, 1962;Lodhi, 1977;Binkley, 1995;Denslow, 1996;Carnevale & Montagnini, 2002). Many authors have shown that such different conditions can affect germination, seed predation, pathogens attacks, tolerance, and herbivory in a species-specific way (Chou & Yang, 1982;Denslow, 1996;Cintra, 1997;Wardle & Lavelle, 1997;Metcalfe & Turner, 1998;Nicotra et al, 1999;Van Oijen et al, 2005). These species-specific biological responses can result in the selection of specific communities of seedlings, soil fauna, bacteria, micorrhiza, and pathogens composition (e.g., see Boettcher & Kalisz, 1990, Dobson & Crawley, 1994Denslow, 1996;Cintra, 1997;Ettema & Wardle, 2002).…”
mentioning
confidence: 99%